Pengaruh Profitabilitas, Nilai Sukuk dan Rating Sukuk terhadap Return Saham Syariah Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024 - Kamaliyah, Fithrah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
This research is motivated by the growing relevance of Islamic financial instruments, such as sukuk, in Indonesia’s capital market. As demand for Sharia-compliant investments increases, understanding the factors influencing Sharia stock performance becomes essential. This study examines the impact of profitability, sukuk value, and sukuk rating on Sharia stock returns among companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. A quantitative approach is used, with financial data collected from annual reports of selected companies through purposive sampling based on Sharia compliance and sukuk issuance criteria. Data analysis is conducted using multiple linear regression, supported by classical assumption and hypothesis tests. The results reveal that profitability and sukuk value have a significant positive effect on Sharia stock returns, while sukuk rating does not show a significant impact. However, collectively, all three independent variables significantly influence Sharia stock returns. These findings imply that investors in Sharia-compliant markets should prioritize a company’s fundamental performance and the scale of sukuk issuance rather than relying solely on sukuk ratings when making investment decisions. Companies aiming to enhance their Sharia stock value should focus on improving profitability and optimizing sukuk structuring to attract ethical investors and strengthen market performance.